Locating potential sources of capacity and vulnerability in geographically remote areas: Reflections based on three case studies. (September 2021) - Hamza, Mo; Eriksson, Kerstin; Staupe-Delgado, Reidar
Abstract: The relationship between geographical and social forms of remoteness and the concepts of vulnerability and capacity remains unclear. Recognising that capacities and vulnerabilities tend to co-exist in a population, the article assumes that the dynamics between these concepts are situational. In this article we draw on three cases to analyse the issue. An Arctic case study provides insight on remoteness in terms of latitude, followed by an Andean case study reflecting on the role of altitude, and lastly an Island community case study provides a perspective on external isolation (recognising that island communities are also typically connected). From these cases we glean a number of preliminary insights for further investigation. One is that remote communities tend to avoid dependence on external actors when possible. Second, power dynamics between remote communities and centralised actors can make disaster management difficult if local capacities are overrun but trust is not present. Third, remoteness mainly becomes a direct source of vulnerability if remoteness translates into neglect, rendering places 'peripheral'. Generalisable insights suggest that relationships take time to build and cannot be easily established after the fact. The cases hence suggest that remote areas typically have a strained relationship with centralised authorities which fosters local coping strategies but also a fear of external dependence, which may ultimately prove problematic in times of adversity.